Targeting DCs for Tolerance Induction: Don’t Lose Sight of the Neutrophils - Hafkamp, Florianne M. J.; Groot Kormelink, Tom; de Jong, Esther C. (Frontiers in Immunology, 2021)
Chronic inflammatory disorders (CID), such as autoimmune diseases, are characterized by overactivation of the immune system and loss of immune tolerance. T helper 17 (Th17) cells are strongly associated with the pathogenesis of multiple CID, including psoriasis, rheumatoid arthritis and inflammatory bowel disease. In line with the increasingly recognized contribution of innate immune cells to the modulation of dendritic cell (DC) function and DC-driven adaptive immune responses, we recently showed that neutrophils are required for DC-driven Th17 cell differentiation from human naive T cells. Consequently, recruitment of neutrophils to inflamed tissues and lymph nodes likely creates a highly inflammatory loop through the induction of Th17 cells that should be intercepted to attenuate disease progression. Tolerogenic therapy via DCs, the central orchestrators of the adaptive immune response, is a promising strategy for treatment of CID. Tolerogenic DCs could restore immune tolerance by driving regulatory T (Treg) cell development in the periphery. In this review, we discuss the effects of tolerogenic adjuvants vitamin D3 (VD3), corticosteroids (CS), and retinoic acid (RA) on both DCs and neutrophils and their potential interplay. We briefly summarize how neutrophils shape DC-driven T cell development in general. We propose that for optimization of tolerogenic DC therapy for the treatment of CID, both DCs for tolerance induction and the neutrophil inflammatory loop should be targeted, while preserving potential Treg enhancing effects of neutrophils.